Contemporary art and left-wing populism: the Artist Taxi Driver as working class ideology. (2nd January 2018) - Kompatsiaris, Panos
ABSTRACT: Philosophical aesthetics is routinely grounded upon a binary opposition separating art, a reflective and contemplative activity, from popular culture, the brute and philistine cultural expressions of the masses. While art is expected to have a broadly conceived educational mission, it has to simultaneously denounce such popular culture forms that involve propaganda, didacticism and immediacy in order to legitimize itself socially. This paper explores the social and political implications of art and left-wing populism through the work of the British artist and taxi driver Mark McGowan and his project Artist Taxi Driver . Employing a direct language and an aggressive anti-neoliberal rhetoric grounded on widespread populist binaries, such as the 'elites' and the 'people', McGowan enacts a militant artistic persona in his series of YouTube videos. His daily commentary on subjects such as the Greek crisis, the Scottish referendum and the Jeremy Corbyn election both challenges the split between art and popular culture and mobilizes this split as a populist negation of prevalent forms of governance.